Paris dans les récits de voyage d’écrivains arabes : repérage, analyse sémantique et cartographie de toponymes - Motasem Alrahabi; Carmen Brando; Muhamed AlKhalil; Joseph Dichy (Humanités Numériques)
We present in this paper an automated method to map out positive or negative semantic modalities associated with place names in Arabic travelogue literature. This research sits at the crossroads of Natural Language Processing, Literary Studies, and Digital Humanities. Our pipeline identifies place named entities, analyzes their semantic context (with regard to opinions, sentiments and emotions), and locates the place names on geographic maps. Our corpus includes six travel writings on Paris from some of the most influential Arab writers of the 19th and 20th centuries. We evaluate rule-based and machine-learning approaches for their efficacy in named entity recognition and semantic analysis. The results of our automated analysis confirm, to a great extent, the judgements and interpretations of traditional critical scholarship on these Arabic literary texts.